Lactobacillus rhamnosus LRa05 improves lipid accumulation in mice fed with a high fat diet via regulating the intestinal microbiota, reducing glucose content and promoting liver carbohydrate metabolism. Issue 11 (16th October 2020) - Sun, Mengzhen; Wu, Tao; Zhang, Guohua; Liu, Rui; Sui, Wenjie; Zhang, Maomao; Geng, Jieting; Yin, Jinjin; Zhang, Min
Abstract : LRa05 resists obesity via ameliorating Streptococcus level and glucose metabolism, moreover, the positive correlation between Intestinimonas and palmitoyl ethanolamide and the negative correlation between Enterorhabdus and vitamin B2 are first found. Abstract : To elucidate the anti-obesity effect of Lactobacillus rhamnosus LRa05 through the analysis of gut microbiota and liver metabolomics, we investigated changes in gut microbiota and liver metabolomic phenotypes in mice by 16S ribosomal RNA gene sequencing and ultraperformance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry. C57BL/6J male mice were orally administered with LRa05 for 8 weeks. Body weight, serum lipid levels, and the lipid accumulation of liver cells and epididymal fat tissues in the mice fed with a high-fat diet were inhibited after treatment with LRa05 at 1 × 10 9 CFU per day per mouse. LRa05 also reshaped the gut microbiota, reduced the abundance of the pro-pathogen bacterial Streptococcus, suppressed blood and liver glucose content, and promoted liver carbohydrate and energy metabolism. Moreover, Intestinimonas and palmitoyl ethanolamide exhibited a positive correlation, whereas Enterorhabdus and vitamin B2 showed a negative correlation. Therefore, LRa05 can potentially be used as an anti-obesity probiotic in further interventions.